Financial Literacy Education for Women: A Novel Approach based on Social Media Platform - Anggita Leviastuti; Tiara Devi Santika; Ilham Prasetyo (Research Synergy Foundation, 2023)
According to the latest data, the financial literacy index in Indonesia stood at 38%. This figure was definitely an improvement compared to previous years, but was still considerably behind compared to the global standard. Taking into account gender disparity in Indonesia, this figure becomes even more abysmal as the financial literacy index for women is substantially lower than men. To solve this problem, a social media knowledge management framework is proposed to structure and disseminate financial knowledge with the purpose of improving the financial literacy index, especially for women, in Indonesia. This knowledge management platform is supported by a financial education program that has been developed based on the characteristics and needs of typical women in Indonesia. To further substantiate the findings of this study, a series of in-depth interviews were conducted with the aim to acquire a better understanding of various aspects of financial literacy from the perspective of women. In total, 13 women who lived in Bandung were chosen as the main subject of this study based on a judgment sampling technique. Encouragingly, more than three-quarter of the respondents were considered to be well-literate. Digging deeper into the data, however, presents a much more nuanced and complicated insight regarding the behavior of the respondents as most of the respondents simultaneously exhibit a very wide range behavior ranging from discipline to carelessness when managing their money.